Prevalence and severity of pterygium in Somalian male population: Can Khat consumption have a synergistic effect with ultraviolet radiation? (Annals of Medical Research, 2021)
Aim: To investigate the relationship between khat consumption, UV radiation and pterygium among male population in Somalia.Materials and Methods: Between November 2019 and February 2020, 2,200 patients were examined. 146 patients who met the criteria among 335 patients with primary pterygium were included in the study. Ocular examinations were performed using slit-lamp biomicroscope. Patients were evaluated in terms of outdoor work, age, medical treatment history of pterygium, use of glasses or hats, family history, location of pterygium and eye with pterygium.Results: In this study, 146 patients with pterygium were examined. The cases were divided into two groups as grade 3 (42 patients, 28.8%) and non-grade 3 (104, 71.2%). The mean age of the patients was 43.5 ± 9.7 years. When the demographic findings of grade 3 and non-grade 3 patients were compared, khat use (p0.001) and outdoor work (p=0.001) were significantly increased in the grade 3 group. The use of sunglasses and / or hats (p=0.004) and medical treatment history (p=0.042) were significantly increased in non-grade 3 groups.Conclusion: Khat consumption may increase the likelihood of advanced grade pterygium. Khat and ultraviolet radiation may have synergistic effects on the pterygium grade.
Keywords: Pterygium; Khat; Catha Edulis; Somalia; Africa